Behavior is a major determinant of predation risk in zooplankton. Issue 2 (2nd February 2017) - Almeda, Rodrigo; van Someren Gréve, Hans; Kiørboe, Thomas
Abstract: Zooplankton exhibit different small‐scale motile behaviors related to feeding and mating activities. These different motile behaviors may result in different levels of predation risk, which may partially determine the structure of planktonic communities. Here, we experimentally determined predation mortality associated with (1) feeding activity (ambush feeders vs. feeding‐current vs. cruising feeders) and (2) mate‐finding behavior (males vs. females). The copepods Oithona nana, O. davisae (ambush feeders), Temora longicornis (feeding‐current feeder), and Centropages hamatus (cruising feeder) were used as prey for different predatory copepods. Copepods with "active" feeding behaviors (feeding‐current and cruising feeders) showed significantly higher mortality from predation ( 2–8 times) than similarly sized copepods with low motility feeding behavior (ambush feeders). Copepod males, which have a more active motile behavior than females (mate‐seeking behavior), suffered a higher predation mortality than females in most of the experiments. However, the predation risk for mate‐searching behavior in copepods varied depending on feeding behavior with ambush feeders consistently having the greatest difference in predation mortality between genders ( 4 times higher for males than for females). This gender‐specific predation pressure may partially explain field observations of female‐biased sex ratios in ambush feeding copepods (e.g., Oithonidae ). Overall, our results demonstrate that small‐scale motile behavior is a key trait in zooplankton that significantly affects predation risk and therefore is a main determinant of distribution and composition of zooplankton communities in the ocean.